Training for Linear Endobronchial Ultrasound Among US Pulmonary/Critical Care Fellowships: A Survey of Fellowship Directors - Tanner, Nichole T. (American College of Chest Physicians, 2013)
BACKGROUND: Endobronchial ultrasound (EBUS) has revolutionized the ability of bronchoscopists to visualize and sample structures surrounding the tracheobronchial tree. It has been shown to be safe, minimally invasive, and highly accurate in the staging and diagnosing of mediastinal diseases. A prior survey of pulmonary fellowship program directors conducted in 2004 showed that only 2% of programs offered EBUS training. METHODS: Surveys were mailed to 154 pulmonary/critical care fellowship directors in the United States and Puerto Rico. Demographics of the fellowship and details of EBUS training were recorded. A comparison of EBUS volume was made between programs with and without an identifiable interventional pulmonologist (IP). RESULTS: The survey response rate was 71%. EBUS equipment was available at 89% of programs. Of those without EBUS, 100% expressed the goal of obtaining equipment within the year. An identifiable IP was present in 70% of programs. This was associated with more EBUS procedures performed by trainees (P < .01). Only 30% of programs have a formal protocol in place to evaluate EBUS competency. Conventional transbronchial needle aspiration is routinely taught in 89% of fellowship programs. CONCLUSIONS: EBUS exposure has rapidly disseminated into fellowship training programs, and programs with an identifiable IP are more likely to provide fellows with more EBUS procedures. The findings of this survey point out the need to develop a standardized protocol for EBUS competency that includes current recommendations and may require training with simulation.